The influence of root-end filling materials on bone healing – an experimental study - Gulie Kui, Andreea; Berar, Antonela; Lascu, Liana; Bolfa, Pompei; Bosca, Bianca; Mihu, Carmen; Baciut, Mihaela; Avram, Ramona; Badea, Mândra (Medicine and Pharmacy Reports, 2014)
Aims. The aim of this experimental study is to assess the bone healing phenomenon produced in the presence of several dental materials: a polycarboxylate cement, a glass-ionomer cement, a composite resin and MTA (mineral trioxide aggregate) based cement. Methods. The biocompatibility of four root-end fillings materials, used in periapical surgery was investigated after intra-osseous implantation of the materials in rats’ calvaria. Tissue reaction was studied at 2, 4, 6, 8, 10 and 12 weeks after implantation. We took into consideration the presence of inflammatory cells (polymorphonuclear leukocytes, macrophages, plasma cells, lymphocytes and giant cells) and classified the aspects of the histological samples according to the following scale: 0 - no inflammation, 1 – mild, isolated inflammation, 2 - moderate, localized inflammatory reaction, 3 - severe, diffuse and intense inflammatory reaction. Results. The inflammatory reaction was present at the six intervals for all the tested materials, but at 12 week interval, the reaction was minimal in all cases. Also, a dissolution reaction was observed for all the materials, less intense for glass-ionomer cement and polycarboxilate cement. Conclusions. At the end of the experimental period, glass-ionomer cement and polycarboxilate cement suffered a lesser dissolution reaction as compared to the second group of tested materials.